Seroprevalence of hepatitis C virus infection in patients with type 2 diabetes mellitus is associated with increased age in sub-Saharan Africa: Results from a cross-sectional comparative analysis - Feutseu, Charly; Kowo, Mathurin Pierre; Boli, Anne Ongmeb; Katte, Jean Claude; Guewo-Fokeng, Magellan; Zemsi, Sylvain; Dehayem, Mesmin Yefou; Choukem, Simeon Pierre; Sobngwi, Eugene (Frontiers in Gastroenterology, 2023)
Background Several epidemiological studies have established the association between hepatitis C virus (HCV) infection and type 2 diabetes mellitus (T2DM). However, the determinants and reasons for the high prevalence of HCV infection in people with T2DM are not well understood especially in sub-Saharan African populations. In this study, we aimed to assess determinants of the association between HCV infection and T2DM. Methods We performed a cross-sectional study amongst 442 T2DM patients recruited from an out-patient adult diabetes clinic in a tertiary hospital and 442 non-diabetic controls recruited from the general population. Serological testing for HCV antibody was performed using standard ELISA technique. Anti-HCV antibody prevalence was reported by age group in participants with diabetes and the non-diabetic controls. Logistic regression was used to examine for factors associated with the HCV infection in patients with diabetes. Results We reported an overall HCV prevalence of 11.5% [95% CI: 9.4-13.6] irrespective of diabetes status in this study. The seroprevalence of HCV infection in diabetics patients was 17.6% [95% CI: 14.0-21.2] compared to 5.5% [95% CI: 3.4-7.6] in non-diabetics (p< 0.001). We did not find a significant HCV seropositivity difference in diabetic patients with common risk factors of HCV infection. When investigating the HCV seroprevalence by age group in diabetic and non-diabetic patients, no case of HCV infection was found in patients less than 30 years old while the highest HCV seropositivity was reported in patients older than 60 years (36.7% T2DM and 11.1% for non-diabetics) followed by the patients belonging to 50-59 years age group (16% in T2DM and 5.8% in non-diabetics) and those in 40-49 years age group (4.4% in diabetic, 0.8% in non-diabetic). To support this finding, in a multivariate logistic regression, only diabetic patients belonging to age group > 65 years had a significant risk (OR: 16.7 [95% CI: 1.7-160.0]) to acquire HCV infection. Conclusion The seroprevalence of HCV infection is higher among T2DM adult patients than in non-diabetic patients, and is associated with increased age. This age-dependent association may suggest a generational exposure that may no longer exist overtime.